TARGET SETTINGS IN THE TEAM: CLARITY OF GOALS AND PERFORMANCE TEAMS IN THE PUBLIC SECTOR - Kasmiah (P3M Stia Al Gazali Barru and Meraja media, 2019)
[Full Paper] to pdf Copyright (c) 2019 Meraja journal